(untitled) (Research, Society and Development, 2022)
It aims to develop the theoretical model of care for the elderly in the RAS that has guided the Family Health Strategy. The study was carried out qualitatively, adopting the Teoria Fundamentada em Dados (TFD) or Grounded Theory (GT), by Strauss and Corbin, and as a theoretical framework, Symbolic Interactionism (SI). The individual interview was adopted as an instrument. With the help of ATLAS/ti 7.0 software, the open coding of the 44 interviews with professionals raised different codes that were grouped according to their similarity, giving rise to 387 preliminary codes, and categorized into fifteen subcategories and five categories. The theoretical model presented in this study consists of the representation of the phenomenon “Building the care network for the elderly, from the perspective of the FHS.” It can be seen with the construction of the theoretical model, that the professionals of the FHS do not follow a protocol of care in the network, that this is defragmented and disjointed. In this study, the development of the theoretical model can support the construction of a model of care for the elderly in the RAS, which more effectively considers the reality of health services and is focused on the demands, needs and rights of the elderly in their context. of life.